(untitled) (Baghdad Science Journal, 2015)
Some new complexes of 4-(5-(1,5-dimethyl-3-oxo-2-phenyl pyrazolidin-4- ylimino)-3,3-dimethyl cyclohexylideneamino) -1,5- dimethyl-2- phenyl -1H- pyrazol -3(2H) –one (L) with Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Pd(II), Re(V) and Pt(IV) were prepared. The ligand and its metal complexes were characterized by phisco- chemical spectroscopic techniques. The spectral data were suggested that the (L) as a neutral tetradentate ligand is coordinated with the metal ions through two nitrogen and two oxygen atoms. These studies revealed Octahedral geometries for all metal complexes, except square planar for Pd(II) complex. Moreover, the thermodynamic activation parameters, such as ?E*, ?H, ?S, ?G and K are calculated from the TGA curves using Coats –Redfern method. Hyper Chem -8 program has been used to predict structural geometries for compounds in gas phase. The heat of formation (?Hf) and bin ding energy (?Eb) at 298 °K for the free ligand and its metal complexes were calculated by PM3 method. The synthesized ligands and their metal complexes were screened for their biological activity against bacterial species, two Gram positive bacteria (Bacillus subtilis and Staphylococcus aureus) and two Gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa).